Community Health Workers. Reinforcement of an Outreach Strategy in Rural Areas Aimed at Improving the Integration of HIV, Tuberculosis and Malaria Prevention, Screening and Care Into the Health Systems. “Proxy-Santé” Study - Moh, Desmorys Raoul; Bangali, Maika; Coffie, Patrick; Badjé, Anani; Paul, Adahourman Aman; Msellati, Philippe (Frontiers in Public Health, 2022)
Background In Côte d'Ivoire, the health system remains poorly accessible and inefficient, particularly in rural areas. Malaria, tuberculosis and HIV remain a major concern. Tasks shifting to Community Health Workers (CHWs) in rural areas has been proposed in terms of responses and has shown encouraging results with some limitations. Objective is therefore to develop and implement, in a health district, at the level of a neighborhood, a sub-prefecture, two villages and two camps, innovative strategies aimed at improving the integration of HIV, malaria and tuberculosis prevention and care into the health system at the community level through CHWs. Methods Introduce innovations to be integrated into the national system: (i) Selection and strengthening of the capacities of CHWs to provide care for the three diseases through home visits [Information Education and Counseling/Communication for Behavior Change (IEC/CBC)], simple malaria screening and management, referral of suspected tuberculosis cases and Directly Observed Treatment, short-course (DOTS), screening, prophylaxis and distribution of antiretrovirals (ARVs) to HIV-infected patients; (ii) monthly animation of village health committees by target groups (women of childbearing age, children under 5 years old, young adolescents); (iii) use of an application and tablets for data collection. Discussion This innovative project integrates new activities such as ARV distribution by CHWs, management of pre-exposure prophylaxis in rural areas and electronic data capture by communities. Several lessons can be learned on the relevance of the role and activities to be carried out by these CHWs in the fight against these three diseases.